2008
DOI: 10.2147/vhrm.s3020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the vasodilating beta-blocker nebivolol on smoking-induced endothelial dysfunction in young healthy volunteers

Abstract: Objective:To assess the effect of nebivolol, a highly selective third generation β 1 -adrenoceptor antagonist with an endothelium-dependent vasodilatory action, on smoking-induced endothelial dysfunction. Research design and methods:This open-label study examined the effect of 14 daily doses of 5 mg nebivolol on forearm blood fl ow in 21 healthy, young, male, light smokers (Յ5 cigarettes/day), measured by plethysmography on Days 1, 7, and 14. The primary endpoint was the difference in forearm blood fl ow after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…However, it is not clear whether cigarette smokers and nonsmokers had the same treatments for the underlying diseases. It has been shown that treatments for cardiovascular diseases such as statins, ␤-blockers, and angiotensin-converting enzyme inhibitors ameliorate endothelial function not only in patients with the target diseases but also in chronic smokers (6,43,48). While we assume that all patients regardless of cigarette smoking had been treated with medications before surgery that could potentially restore microvascular function, we cannot rule out the possible influence of treatments.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not clear whether cigarette smokers and nonsmokers had the same treatments for the underlying diseases. It has been shown that treatments for cardiovascular diseases such as statins, ␤-blockers, and angiotensin-converting enzyme inhibitors ameliorate endothelial function not only in patients with the target diseases but also in chronic smokers (6,43,48). While we assume that all patients regardless of cigarette smoking had been treated with medications before surgery that could potentially restore microvascular function, we cannot rule out the possible influence of treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Nebivolol/HCTZ and metoprolol/HCTZ both lowered high-density lipoprotein (HDL)cholesterol and increased triglyceride levels, but only metoprolol/HCTZ tended to increase HOMA-IR. Clinical evidence for the vasodilating properties of nebivolol in humans results primarily from forearm blood flow studies [10,11,[30][31][32]. This has been attributed to a decrease in aortic wave augmentation through attenuation of pulse wave reflection by peripheral vasodilatation [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with higher initial values experienced greater reductions in HR and BP compared with patients having moderately elevated initial values 99. In other clinical trials, nebivolol reduced vascular resistance and improved endothelial function in patients with hypertension, and also lowered the levels of the inflammatory marker, high-sensitivity C-reactive protein, in healthy volunteers who smoked cigarettes 100,101…”
Section: Heart Rate Control In Hypertensionmentioning
confidence: 96%